2009
DOI: 10.1029/2008jd010608
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the nonmigrating semidiurnal tide above Antarctica observed from the TIMED Doppler Interferometer

Abstract: [1] Spatial structure and temporal evolution of the nonmigrating semidiurnal tidal components over Antarctica are determined by analyzing horizontal wind measurements in the Mesosphere and Lower Thermosphere (MLT) collected using TIMED Doppler Interferometer (TIDI) on the NASA Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite from 2002 to 2007. The data were organized into six specific intervals of approximately 60 days corresponding to the TIMED yaw periods. The results confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Murphy (2002) has demonstrated how this behaviour can result from the constructive and destructive interference between a migrating and non-migrating tide. Previous multi-station ground-based and satellite studies have shown that the semidiurnal tide is composed of a mixture of migrating and non-migrating components at high southern latitudes (Murphy et al, 2006;Baumgaertner et al, 2006;Iimura et al, 2009;Hibbins et al, 2010) away from the pure S = 1 westwards propagating wave seen at the South Pole (Forbes et al, 1995). Although the single-site observations presented here are incapable of resolving the migrating from the non-migrating components of the semidiurnal tide, the seasonal behaviour of the 12-h wave provides strong observational evidence that the Southern Hemisphere non-migrating components extend further equatorwards than previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murphy (2002) has demonstrated how this behaviour can result from the constructive and destructive interference between a migrating and non-migrating tide. Previous multi-station ground-based and satellite studies have shown that the semidiurnal tide is composed of a mixture of migrating and non-migrating components at high southern latitudes (Murphy et al, 2006;Baumgaertner et al, 2006;Iimura et al, 2009;Hibbins et al, 2010) away from the pure S = 1 westwards propagating wave seen at the South Pole (Forbes et al, 1995). Although the single-site observations presented here are incapable of resolving the migrating from the non-migrating components of the semidiurnal tide, the seasonal behaviour of the 12-h wave provides strong observational evidence that the Southern Hemisphere non-migrating components extend further equatorwards than previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the summer months, the Southern Hemisphere tide is well represented by the model, but during November to March the model consistently over estimates the strength of the semidiurnal tide. Comparison between the non-migrating modes of the semidiurnal tide in the high latitude North and South Hemisphere reveals substantially weaker non-migrating tides in the north (Iimura et al, 2009. Thus the migrating tide will be more dominant in the north and the constructive/destructive interference between the migrating and nonmigrating tides at high latitudes will be less pronounced than that observed in the south (e.g.…”
Section: Comparison With Equivalent Northern Latitude Datamentioning
confidence: 99%
“…Na and Fe densities measured by broadband resonance fluorescence lidars were also used to observe wave dynamics in the Antarctic mesopause region [ Nomura et al , ; Collins and Gardner , ; Diettrich et al , ], but none of them depicted persistent 3–10 h waves. Gravity waves and large‐scale global waves such as tides and planetary waves in the Antarctic MLT have also been studied by satellite observations [e.g., Iimura et al , ; Morris et al , ; McDonald et al , ]. There are several explanations for the lack of evidence for persistent 3–10 h waves in the observations mentioned above: (1) horizontal winds are usually dominated by tides, thereby obscuring these wave signatures, (2) nonrange‐resolved temperature, wind, and airglow data would have easily mistaken these phenomena as tides because no vertical wavelength information was available, and (3) most observations in the past did not have sufficient temporal resolution or time span to reveal these waves deterministically.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous observations of the nonmigrating SW1 mode in the SH (e.g., Forbes et al 1995;Portnyagin et al 1998;Murphy et al 2003Murphy et al , 2006Aso 2007;Chang et al 2009;Hibbins et al 2010;Iimura et al 2009). Yamashita et al (2002) reproduced the relationship between the SH semidiurnal nonmigrating tides and the NH stratospheric planetary waves in an atmospheric circulation model.…”
Section: Teleconnections Involving Tidesmentioning
confidence: 99%